(untitled) (Journal of Atomic and Molecular Sciences, 2010)
A mathematical rate equation model using a Monte Carlo simulation has been used to analyze the laser optogalvanic signals of neon waveforms excited at 638.3 nm and 650.7 nm and arising from the 1s_4 state transitioning to 2p_7 and 2p_8 states, respectively. The decay rates have been determined for the directly involved 1s_4 state and also for the indirectly involved 1s_2 and 1s_5 states. There is good agreement among the decay rate constants found and they show a predominantly linear variation with increasing current.